The interference of the Digital Influencer in the contemporary advertising - Negri , Marina A. E. (Seven Editora, 2023)
This article seeks to draw a parallel between the exercise of Advertising as it is traditionally known, as a massive communication activity, focused on the dissemination of products and services, and advertising made by Digital Influencers, a practice, in the stake, directed to specific audiences, a model now in vogue and high repercussion in contemporary times.  The deed addresses results obtained by advertising brands that migrated from the orthodox format, strategies that merge / Denotation óInformation/ and /  Emotion Connotation/, to the current óstandard /Digital Influencers  Personal Opinionsó/, to get closer to more up-to-date and extensive and their target public and get more persuasive strength about their purchasing decisions.DOI: https://doi.org/10.56238/devopinterscie-062